Mixed-metal amide catalysts for ammonia decomposition applications - Kirk, C (2019)
Our current reliance on fossil fuels is highly unsustainable due to their limited supply and environmental impact. There is an urgent global need to revolutionise the way in which we source and store our energy. Hydrogen is undoubtedly going to play a role in re-designing the transportation sector in particular, but there are significant barriers preventing its widespread implementation. The reversible chemical storage of hydrogen as ammonia provides all the benefits of hydrogen as a fuel, whilst also having characteristics enabling some of the challenges faced by hydrogen to be overcome.